Merkel cell polyomavirus status is not associated with clinical course of Merkel cell carcinoma - Schrama, David; Ludwig-Peitsch, Wiebke; Zapatka, Marc; Kneitz, Hermann; Houben, Roland; Eib, Steffi; Haferkamp, Sebastian; Moore, Patrick S.; Shuda, Masahiro; Thompson, John F.; Trefzer, Uwe; Pföhler, Claudia; et al. (The journal of investigative dermatology, 2011)
The majority of Merkel cell carcinomas (MCCs) are associated with the recently identified Merkel cell polyomavirus (MCV). However, as it is still unclear to which extent the presence of MCV impacts tumor characteristics or clinical outcome, we correlated the MCV status of tumor lesions obtained from 174 MCC patients including 38 MCC patients from Australia and 138 MCC patients from Germany with clinical characteristics, histomorphology, immunohistochemistry, and course of the disease. MCV DNA was present in 86% of MCCs and, in contrast to previous reports, no significant difference in MCV prevalence was present between Australian and German MCC cases. When patients were stratified according to their MCV status, only tumor localization (P=0.001), gender (P=0.024), and co-morbidity, i.e., frequency of patients with previous skin tumors (P=0.024), were significantly different factors. In contrast, year of birth and diagnosis, age at diagnosis, or histological type and features representing the oncogenic phenotype such as mitotic rate or expression of p16, p53, RB1, and Ki67 were not significantly different between MCV-positive and MCV-negative MCCs. MCV status also did not influence recurrence-free, overall, and MCC-specific survival significantly. In summary, although MCV-positive and MCV-negative MCCs may have different etiologies, these tumors have comparable clinical behaviors and prognosis.
Gesehen am 26.10.2022